Gambaran Tingkat Pengetahuan Remaja SMA Hangtuah Tarakan Mengenai HIV/AIDS Tahun 2024 - Lily Herawati (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
HIV (Human Immunodeficiency Virus) is a virus that weakens the human immune system and leads to AIDS (Acquired Immune Deficiency Syndrome). Since the beginning of the epidemic, more than 70 million people have been infected with the HIV virus, and 35 million people have died due to HIV. The majority of HIV and AIDS cases still occur in the productive age population (15-49 years), where transmission is most likely to occur during adolescence. Objective: To determine the level of knowledge about HIV/AIDS among high school students at Hangtuah Tarakan in 2024. The research method used is descriptive survey, and the sample is taken through purposive sampling. The sample in this study consists of 120 respondents, all of whom are tenth-grade students at Hangtuah Tarakan High School. The research results show that based on the age frequency, the highest number of mid-adolescents aged 14-16 years is 97 respondents (80.8%), the highest gender characteristic is female, with 68 respondents (56.7%), the characteristic based on the most common source of information is social media (internet, TV, newspapers) with 86 respondents (71.7%), and the characteristic with the highest level of knowledge is good knowledge, with 69 respondents (57.5%). The conclusion of the research results is that the level of knowledge about HIV and AIDS in Hangtuah Tarakan High School is mostly good, as found in 120 respondents